What is Europe? Second Edition - Triandafyllidou, Anna (Taylor & Francis, 2023)
This authoritative yet accessible introduction to understanding Europe today moves beyond accounts of European integration to provide a wide-ranging and nuanced study of contemporary Europe and its historical development. This fully updated edition adds material on recent developments, such as Brexit and the migrant and Eurozone crises. The concept of Europe is instilled with a plethora of social, cultural, economic, and political meanings. Throughout history, and still today, scholars writing on Europe, and politicians involved in national or European politics, often disagree on the geographic limits of this space and the defining elements of Europe. Europe is, therefore, first and foremost a concept that takes different shapes and meanings depending on the realm of life on which it is applied and on the historical period under investigation. At a given point in time, depending on the perspective we adopt and the situation in which we find ourselves, Europe may represent very different things. Thus, we should better talk about 'Europes' in plural. What is Europe? explores these evolving conceptions of Europe from antiquity to the present. This book is all the more timely as Europe responds to the Russian invasion of Ukraine and Britain's departure from the European Union, financial slump, refugee emergencies, and the COVID-19 pandemic. This book offers a fully updated introduction to European studies from an interdisciplinary perspective. It is a crucial companion to any undergraduate or graduate course on Europe and the European Union.